Do the Spanish courts have jurisdiction (international and domestic) to modify a maintenance decision in cross-border cases? - Marchal Escalona, Nuria (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Complexity is one of the innate characteristics of private international law. Knowing what problems are posed by international private relations and how they are resolved is, nowadays, a subject still pending for many of our Courts and Tribunals, as is demonstrated by the Judgment handed down by the Provincial Court of Cáceres on 29 May 2023. It reveals errors that, far from being simple and understandable, are inexplicable and inconceivable. It demonstrates not only a lack of knowledge of the most basic concepts of our discipline, but also of the sources that regulate it.
Keywords: International jurisdiction; domestic jurisdiction; modification of a maintenance decision